Pendidikan sebagai pondasi kemajuan bangsa - Kadrina, Lilatul (Maliki Interdisciplinary Journal, 2025)
Education has a crucial role in supporting the nation's progress through improving the quality of productive, creative and innovative human resources. With education, individuals not only gain intellectual knowledge, but also moral values that form a character with integrity. In the context of globalization, education is the key to creating a competent workforce and supporting economic growth and reducing social inequality. In Indonesia, programs such as BOS and KIP have increased access to education in remote areas. However, the main challenges to Indonesia's education system include gaps in access, quality of education, and misalignment of the curriculum with the needs of the world of work. The COVID-19 pandemic has also exacerbated inequality in access to education. Therefore, a holistic approach is needed that includes improving educational infrastructure, teacher training and relevant curricula to overcome these challenges and realize inclusive and sustainable education.